Identification of Musculoskeletal Disorders in Garment Workers using the Nordic Body Map (NBM) - Aprilia Herlinawati; Doni Alhasfi; Talitha Irmadella Radhwa Ariyanto; Dessy Yasnia Hapsari; Ameylia Devi Ardianingsih; Nadya Nur Rizqia; Zulaikha Suparman Gunawan (Universitas Negeri Semarang, 2025)
The textile industry is one of the industrial activities that is carried out repeatedly with static positions and has non-ergonomic rules, causing musculoskeletal disorders such as stiff neck, back pain, muscle pain in the shoulder and calf areas. These complaints can reduce work productivity in garment workers. This study aims to determine the musculoskeletal disorders experienced by garment workers x. This study was conducted through direct observation, interviews, and filling out the Nordic Body Map (NBM) questionnaire to measure musculoskeletal disorders. The results showed that the most complaints of pain were in the waist, upper neck, and the back. For the classification of risk levels based on the Nordic Body Map score, 17 respondents (85%) experienced a risk level of MSDS disorders with the